The visit of an all-party group of Members of Parliament to Spain : report - Crawford Greene, W. P. ; Grenfell, D. R. (David Rhys), 1881-1968 ; James, A. W. ; Macnamara, J. R. J. ; Roberts, Wilfrid; Cocks, F. Seymour (Frederick Seymour), b. 1882 (1936)
1936 018b-0074-009 292/946/18b/74(ix)